Illustrated type specimens catalogue of Recep Tayyip Erdogan University Zoology Museum of the Faculty of Fisheries - Kaya, Cüneyt; Bayçelebi̇, Esra; Turan, Davut (Zootaxa, 2021)
The first type specimens catalogue of Recep Tayyip Erdogan University Zoology Museum of the Faculty of Fisheries, Rize (FFR) is presented. The catalog includes 3030 specimens from 249 lots, representing 55 holotypes and 2974 paratypes of 62 nominal species. Corrections and comments on the original descriptions are included in the remarks for each species if necessary. The current distribution range of all species is given. Photos of all holotypes and one paratype of each nominal species are presented to show the current condition of the types.